Multidisciplinary Management of Recurrent Aphthous Stomatitis Triggered by Severe Depression - Nur Tsurayya Priambodo; Hening Tuti Hendarti; Azimatul Kharimah (Denta Journal Kedokteran Gigi, 2021)
Background: Recurrent Aphthous Stomatitis (RAS) is an inflammation of the oral mucosa in the form of a single or more ulcer that occurs repeatedly. One of the predisposing factors that contribute to the onset of RAS is depression. Depression is a mood that is not happy or sadness that is experienced as part of the pattern of life. Objective: Discuss multidisciplinary management in cases of 65-year-old women with large multiple ulcers with depression-triggering factors. Case: Women aged 65 years complained of recurrent canker sores. The frequency of RAS increased by 10 years due to economic and household problems. It has been treated with topical non-steroidal anti-inflammatory drugs but does not heal. Does not have a history of systemic diseases. Case Management: Do investigations are complete peripheral blood examination, Depression Anxiety Stress Scale (DASS), Refer patients to the psychiatric specialist. Multidisciplinary treatment is performed by a psychiatric specialist. Treatment of oral mucosa with topical anti-inflammatory steroid drugs. Conclusions: in accordance with the treatment that has been given, this case has recovered after day 14. So it can be concluded that proper multidisciplinary management and elimination of triggering factors are the main roles to prevent recurrence and reduce the frequency of recurrent aphthous stomatitis.